2019
DOI: 10.1140/epjc/s10052-019-7014-y
|View full text |Cite
|
Sign up to set email alerts
|

Light-cone sum rules analysis of $$\Xi _{QQ^{\prime }q}\rightarrow \Lambda _{Q^{\prime }}$$ weak decays

Abstract: We analyze the weak decay of doubly-heavy baryon decays into anti-triplets Q with light-cone sum rules. To calculate the decay form factors, both bottom and charmed anti-triplets b and c are described by the same set of leading twist light-cone distribution amplitudes. With the obtained form factors, we perform a phenomenology study on the corresponding semi-leptonic decays. The decay widths are calculated and the branching ratios given in this work are expected to be tested by future experimental data, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…To study semilep-tonic decay width of doubly heavy baryons, we use the following relations according to Ref. [25]: (20) which are related to semileptonic decay widths of doubly heavy baryons with states 1/2 to 1/2, 1/2 to 3/2 and also…”
Section: Semileptonic Decays Of Double Heavy Baryonsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study semilep-tonic decay width of doubly heavy baryons, we use the following relations according to Ref. [25]: (20) which are related to semileptonic decay widths of doubly heavy baryons with states 1/2 to 1/2, 1/2 to 3/2 and also…”
Section: Semileptonic Decays Of Double Heavy Baryonsmentioning
confidence: 99%
“…As there are more doubly heavy baryons may be confirmed and discovered experimentally in the future, the theoretical studies about them are essential. They need to study from the theoretical investigation based on quark models [5][6][7][8][9][10][11][12][13], Heavy Quark Spin Symmetry [14,15], QCD Sum Rules [16][17][18], lata e-mail: s.rahmani120@gmail.com (corresponding author) tice QCD [19], Light-cone sum rules [20] and Bethe-Salpeter equation approach [21]. Brodsky et al found that the large SELEX value of the isospin splitting of the cc states implies that double charm baryons are very compact [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the most serious problem is the "shuttle effect". So far, many strategies have been proposed and developed to address the issue [5][6][7][8][9][10][11][12] . The most popular one is to inhibit the diffusion of polysulfides by increasing the physical and chemical adsorption ability of conventional sulfur-based cathode material, but can only restrain the polysulfides shuttle effect to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…The X‐ray structure of 3d is shown in Figure . However, strong electron‐donating groups are not compatible in this system, implying a Friedel–Crafts‐type oxidation process ( 3c ) . Functional groups at the meta or ortho positions do not affect the reaction ( 3l – 3n ).…”
Section: Resultsmentioning
confidence: 92%